UV irradiation analysis of complementation between, and replication of, RNA-negative temperature-sensitive mutants of Newcastle disease virus. - Peeples, M E (1982)
Random UV irradiation-induced lesions destroy the infectivity of Newcastle disease virus (NDV) by blocking downstream transcription from the single viral promoter. The nucleocapsid-associated polypeptides most likely to be involved in RNA synthesis are located at the extreme ends of the genome: NP and P are promoter proximal genes, and L is the most distal gene. We attempted to order the two temperature-sensitive (ts) RNA-negative (RNA-) mutant groups of NDV by determining the UV target sizes for the complementing abilities of mutants A1 and E1. After UV irradiation, E1 was unable to complement A1, a result compatible with the A mutation lying in the L gene. In contrast, after UV irradiation, A1 was able to complement E1 for both virus production and viral protein synthesis, with a target size most consistent with the E mutation lying in the P gene. UV-irradiated virus was unable to replicate as indicated by its absence in the yields of multiply infected cells, either as infectious virus or as particles with complementing activity. After irradiation, ts mutant B1 delta P, with a non-ts mutation affecting the electrophoretic mobility of the P protein, complemented E1 in a manner similar to A1, but it did not amplify the expression of delta P in infected cells. This too is consistent with irradiated virus being unable to replicate despite the presence of the components needed for replication of E1. At high UV doses, A1 was able to complement E1 in a different, UV-resistant manner, probably by direct donation of input polypeptides. Multiplicity reactivation has previously been observed at high-multiplicity infection by UV-irradiation paramyxoviruses. In this case, virions which are noninfectious because they lack a protein component may be activated by a protein from irradiation virions.